2009
DOI: 10.1017/s0021859609008764
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating greenhouse gas mitigation practices in livestock systems: an illustration of a whole-farm approach

Abstract: SU MMARYAs agriculture contributes about 0 . 08 of Canada's greenhouse gas (GHG) emissions, reducing agricultural emissions would significantly decrease total Canadian GHG output. Evaluating mitigation practices is not always easy because of the complexity of farming systems in which one change may affect many processes and associated emissions. The objective of the current study was to compare the effects of selected management practices on net whole-farm emissions, expressed in CO 2 equivalents (CO 2 e) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…can also influence the reported emission reduction estimates. However, this uncertainty in emission reduction estimates cannot be handled with current knowledge since livestock production is complex in nature and varies between countries and production systems (Stewart et al 2009;Crosson et al 2011;Loyon et al 2016). Currently no standard methodology exists to evaluate the quality, representativeness and transitory nature of emission data pertaining to livestock production systems.…”
Section: Selection Of Data Sourcesmentioning
confidence: 99%
“…can also influence the reported emission reduction estimates. However, this uncertainty in emission reduction estimates cannot be handled with current knowledge since livestock production is complex in nature and varies between countries and production systems (Stewart et al 2009;Crosson et al 2011;Loyon et al 2016). Currently no standard methodology exists to evaluate the quality, representativeness and transitory nature of emission data pertaining to livestock production systems.…”
Section: Selection Of Data Sourcesmentioning
confidence: 99%
“…Adding lipids to finishing diets to reduce enteric CH 4 production slightly decreases total GHG emissions of beef production systems (Stewart et al, 2009;Beauchemin et al, 2011;Nguyen et al, 2012a). In this study, adding lipids both to finishing and cow-calf diets (S9) decreased GHG emissions per kg carcass mass by no more than 3%, which was lower than the 11% decrease obtained by Beauchemin et al (2011).…”
Section: Discussionmentioning
confidence: 61%
“…and/or per unit of area occupied. Stewart et al (2009) compared whole-farm emissions per unit of protein output of 11 management systems based, in part, on equations recommended by IPCC. The authors showed that compared to the baseline management scenario, pasturing cattle on alfalfa-grass had the largest decrease (0.39 to 0.66 Mg CO 2 e (Mg protein) −1 ) in emissions for all locations.…”
Section: Net Greenhouse Gases Emissions From Animal Agriculturementioning
confidence: 99%